Children with Haemophilus influenzae type b (Hib) vaccine failure have long-term bactericidal antibodies against virulent Hib strains with multiple capsular loci. Issue 34 (25th July 2016) - Townsend-Payne, Kelly; Ladhani, Shamez N.; Findlow, Helen; Slack, Mary; Borrow, Ray
Highlights: We tested SBA activity in 127 children with Hib vaccine failure in the UK. SBA activity was assessed against Hib strains expressing 1–5 capsulation locus copies. There was no association between SBA titres and number of capsulation locus copies. Children with Hib vaccine failure are protected against multiple-copy Hib strains. Abstract: Children who develop invasive Haemophilus influenzae serotype b (Hib) disease after immunisation with a highly-effective conjugate vaccine are more likely to have been infected with Hib strains possessing multiple copies of the capsulation locus. Using a recently-validated serum bactericidal antibody (SBA) assay, we tested convalescent sera from 127 Hib vaccine failure cases against clinical Hib strains expressing 1–5 copies of the capsulation locus. SBA titres correlated weakly with anti-capsular IgG antibody concentrations and there was no association between SBA geometric mean titres and number of capsulation locus copies. After infection, children with Hib vaccine failure were equally protected against Hib strains with 1–5 copies of the capsulation locus.